Prediction and analysis of Slovakian timber trade on global market conditions - Gejdoš, Miloš; Potkány, Marek (Serbian Journal of Management, 2017)
In Slovakian forestry the main source of finance is the wood sale. The main aim of this paper is to evaluate the assortments supply structure (quality management), prices development for the coniferous sawlogs and to set the future prediction of this development in new global market conditions, which are affected mainly by the global climate changes. Price changes were analysed for the period of the years from 2000 to March 2016 for the spruce and fir sawlogs. Data about the volume supply of raw-wood assortments in Slovakia for years 2005-2014 were collected from “Green Reports“ published by the Ministry of Agriculture and Rural Development of the Slovak Republic. From the influence factors in the studied period, the biggest impact was assigned to the global economic crisis. The prediction captures the further decline of prices of raw-wood assortments. In the second half of the year 2016 the price of sawlogs decreased by € 4 per 1 m3. Local impacts, the structure of wood processors and specific trade area in Slovakia affected substantially the structure of assortments on Market. There is also some space for a better evaluation of harvested wood.